The environment on the Human Rights discourse and policies: a preliminary approach to the state of the question - Sotomayor Trelles, Enrique (2019)
This article proposes a general overview on the complex and multidimensional relationship between human rights and environment issues. However, this relationship requires adetachment from a strictly state-centered perspective, to incorporate enterprises in the interaction that makes it possible to carry out economic activities in a sustainable environment.The paper contains two major sections: a first one that proposes an approach to the research problem from the Inter-American System for the Protection of Human Rights, perspective regarding the recent Advisory Opinion OC-23/17 of the Inter-American Human Rights Court. Moreover, a second section adopts the perspective of public policies to analyze the interrelation between human rights and the environment, and, specifically, through the analysis of three public policies: the National Plan of Environmental Action 2011- 2021, the National Human Rights Plan 2018-2021 and the future National Action Plan on Business and Human Rights.